Nos rastros da “Maria Fumaça”: o ensino de História a partir das fotografias familiares - COSTA, Daniele Barreto da (Universidade Federal do Pará, 2023)
This dissertation establishes the possibility of building and using local history from the reading of students' primary sources, such as photographs, as a means of facilitating the understanding of the contents of History. The place where we developed our study is the School Center in Learning and Development Percepcion (CEADEP), where I have been teaching for 12 years. To develop our purpose, we started from the problematization of the uses, from a heritage perspective, of places / objects / monuments / memory spaces in the city of Castanhal in Pará. spaces of memory, we propose to reflect on historical time (past and present) and problematize them as narratives that emerged as stories of the city, from then onwards we glimpse the possibility of bringing about other narratives. We culminated in the proposition of remembrance of the city using sources available in the personal collections of students, who, in collaboration with their families, made available as a solution for implementing the propositional dimension of this dissertation, the Family Portal, allowing the students themselves to assume the protagonism of the stories told. The use of digital tools to publicize photographs made it possible for them to perceive different forms of treatment and manipulation of photographic records over time, allowing them to analyze how to conserve this type of source, in addition to enabling readings of changes and permanencies that occurred in the city, disputes over what should or should not be remembered, social, political and economic conflicts, as well as perceived forms of appropriation and installation of their families in the city, and the care that must be taken when dealing with historical sources.